2013
DOI: 10.3928/01484834-20121212-02
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Simulation-Based Orientation of Baccalaureate Nursing Students Preparing for Their First Clinical Experience

Abstract: This study evaluated the effectiveness of a 2-day, simulation-based orientation for baccalaureate nursing students preparing to begin their first clinical experience. Students were recruited for participation in the study from a clinical foundation course. Actors (standardized patients) provided students with the chance to engage with simulated real patients in realistic clinical situations prior to entering the clinical setting. Students' perceived stress, knowledge acquisition, anxiety, self-confidence, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 21 publications
1
38
1
2
Order By: Relevance
“…Dearmon, Graves, Hayden, Mulekar, Lawrence, Jones, Smith and Farmer [39] support this finding, having concluded in their study that simulation-based orientation was very useful in preparing nursing students for practice.…”
Section: Discussionsupporting
confidence: 54%
“…Dearmon, Graves, Hayden, Mulekar, Lawrence, Jones, Smith and Farmer [39] support this finding, having concluded in their study that simulation-based orientation was very useful in preparing nursing students for practice.…”
Section: Discussionsupporting
confidence: 54%
“…As reported by Dearmon et al (2013), high levels of anxiety can negatively impact student performance leading to the inability to perform and ultimately jeopardizing patient safety. If students feel less anxious, they may be more likely to establish an enhanced therapeutic relationship with the patient thus achieving the goals of improving patient outcomes and compliance with treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Further, it was reported that simulations improved the confidence of nursing students during training for the discharge of postpartum mothers (Wagner et al, 2009). Reilly & Spratt (2007) and Dearmon et al (2013) identified that simulation-based initiatives increase in students' clinical competence and decrease their stress. Chiang & Chan (2014) reported that simulation provide positive learning environment.…”
Section: Discussionmentioning
confidence: 99%